Aberrant overexpression of vascular endothelial growth factor in pancreatic ductal adenocarcinoma is associated with aggressive clinical behavior - Naomi Y Jiang; Bruce A Woda; Liping Zhang; et al (Dove Medical Press, 2010)
Naomi Y Jiang1, Bruce A Woda2, Liping Zhang2, Suyang Hao2, Karen A Dresser2, Di Lu21Massachusetts Institute of Technology, Worcester, MA, USA; 2Department of Pathology, University of Massachusetts Medical Center, Worcester, MA, USAAbstract: Pancreatic adenocarcinoma is a leading cause of cancer-related deaths in the United States. In this study, we studied vascular endothelial growth factor (VEGF) expression in pancreatic adenocarcinoma by immunohistochemical staining. Clinical follow-up and survival data were analyzed. We determined that VEGF was aberrantly overexpressed in a subset of primary pancreatic adenocarcinoma. Statistically, VEGF overexpression was associated with higher stage, higher grade, and lymph node metastasis (P < 0.001, P = 0.012, and P < 0.005, respectively). Additionally, patients of this subset had a much shorter overall survival than patients without VEGF overexpression, as evidenced by Kaplan–Meier plots and the log-rank test (P = 0.001). The 5-year overall survival rate was 17% in patients with VEGF overexpression compared to 52% in patients without VEGF overexpression. The median survival was only 13 months for patients with VEGF overexpression compared to 65 months for patients without. In conclusion, VEGF is a biomarker that identifies a subset of pancreatic ductal adenocarcinoma with aggressive clinical behavior.Keywords: pancreatic adenocarcinoma, VEGF, cancer